2004
DOI: 10.1111/j.1467-985x.2004.0apm2.x
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Risk-Adjusted Charts

Abstract: The paper provides an overview of risk-adjusted charts, with examples based on two data sets: the first consisting of outcomes following cardiac surgery and patient factors contributing to the Parsonnet score; the second being age-sex-adjusted death-rates per year under a single general practitioner. Charts presented include the cumulative sum (CUSUM), resetting sequential probability ratio test, the sets method and Shewhart chart. Comparisons between the charts are made. Estimation of the process parameter an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
84
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(84 citation statements)
references
References 23 publications
0
84
0
Order By: Relevance
“…In other cases, the in-control rate depends on factors such as patient characteristics and methodological improvements. These cases require the application of a risk adjustment method 12,46,47 . Another important issue in health surveillance problems is that the quality of the baseline data can be readily contaminated by unexplained noise spikes.…”
Section: Discussionmentioning
confidence: 99%
“…In other cases, the in-control rate depends on factors such as patient characteristics and methodological improvements. These cases require the application of a risk adjustment method 12,46,47 . Another important issue in health surveillance problems is that the quality of the baseline data can be readily contaminated by unexplained noise spikes.…”
Section: Discussionmentioning
confidence: 99%
“…A better alternative when small shifts are present are control charts based on cumulative sums (CUSUM). Furthermore, the Shewhart p-chart is found to be less efficient than the CUSUM even when the change in parameter being tested for is large [17]. In this article we will use the so-called algorithmic CUSUM chart.…”
Section: Cusum Charts Based On Sampling Proportionsmentioning
confidence: 97%
“…The aim of considering subgroups is to reduce as much as possible the sources of differences in defective probabilities between samples, other than the variability of the measurement instrument. This idea of evaluating each observation according to the properties of its own population is similar to the idea of the risk-adjusted monitoring [16,17]. For instance, in the case of a PMVI, the subgroups could be made by classifying the cars by age.…”
Section: Total Chart Made From Subgroups P Totalmentioning
confidence: 99%
“…Here, we will concentrate on the RA-CUSUMs, but the reader is referred to the review by Woodall (2002) for other available methods. An early review on RA-CUSUM charts can be found in Grigg and Farewell (2004).…”
Section: Accepted Manuscriptmentioning
confidence: 99%